ANALISIS EFISIENSI ANGGARAN BELANJA DAERAH DENGAN PENERAPAN PERHITUNGAN BIAYA BERBASIS AKTIVITAS PADA KECAMATAN PONTIANAK SELATAN TAHUN ANGGARAN 2013 - B51107110, ANINDITA DESILIA BUSTAMI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This research title is â€œAnalysis of Local Budgeting Expense Ffficiency by application of activity based costing system at South Pontianak District on 2013â€. The aim of this research is to find out whether expenditure standard analysis can provide guides in the right budget planning to avoid excessive or much less budgeting prediction and knowing process of Local Budgeting Expense at at South Pontianak District on 2013 by application of activity based costing system as a rational and measurable method, last purpose to know efficiency of Local Budgeting Expense in South Pontianak District on 2013. Method used in this research is Survey analysis research as applied research. The variable analyzed is the budget of South Pontianak District on 2013. By application of Activity Based Costing System, statistic method utilized is linear regression method. As a result of this research is Local Budgeting Expense using Activity Based Costing Approchment is more efficient on allocation of budgeting at the activity than conventional ways. Keyword : Local Budgeting Expense, Activity Based Costing System